Review of Florida's Teacher Certification System Administered by the Department of Education. Report No. 95-10 - Florida State Legislature, Tallahassee; Florida State Legislature, Tallahassee; Florida State Legislature, Tallahassee. Office of Program Policy Analysis and Government Accountability ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1995)
This report presents the results of a review of Florida's teacher certification system, administered by the Department of Education. The review addressed: (1) how Florida should regulate teachers to ensure that they are professionally qualified and possess the credentials, knowledge, and skills to provide a quality education; (2) who should administer teacher certification; and (3) whether a process has been established to assess whether the current teacher certification system is effectively meeting its intent. Conclusions and recommendations include: Florida would not be assuring that its teachers were professionally qualified if it did not regulate teachers or regulate teachers using registration; the disadvantages of licensure warrant caution; the Department of Education should administer a teacher certification system; Florida needs to establish a thorough certification system; Florida's certification requirements are similar to those of other states; performance measures need to be developed; and the proposed certification system does not include a student performance assessment element. Recommendations focus on: the type of performance-based teacher certification system to adopt; what the State Board of Education needs to ensure when approving a performance-based system; and the need for the Board of Education to develop goals and objectives for teacher certification. The appendix presents a response from the Department of Education. (SM)
Availability: Florida State Legislature, Office of Program Analysis and Government Accountability, 111 West Madison Street, Room 312, Post Office Box 1735, Tallahassee, FL 32302; Tel: 904-488-0021 or Tel: 800-531-2477 (Toll Free); Fax: 904-487-3804.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Elementary Secondary Education; Higher Education; Knowledge Base for Teaching; Preservice Teacher Education; Student Evaluation of Teacher Performance; Teacher Certification; Teacher Competencies; Teacher Evaluation; Teacher Qualifications; Teaching Skills; Florida; Teacher Knowledge; Reports, General